Experimental quantification of genetic and ontogenetic effects on fighting behavior in the broad-horned flour beetle - Toshiki Nishitani; Kentarou Matsumura; Erik Postma; Manmohan Dev Sharma; David J Hosken; Takahisa Miyatake (Behavioral Ecology and Sociobiology, 2024)
Most animal behaviors show large within- and among-individual variation, and this includes competitive male behaviors. With male fighting for example, aggressiveness often correlates with dominance, and contest duration varies with age. However, few studies have directly quantified how mean aggressiveness and contest duration, the variation among individuals in both traits, and the relationship among them, vary with age. Here we address these gaps and examine the effect of male age and genotype on two key aspects of male fighting behavior - aggressiveness (here measured as latency to fight) and contest duration - and the relationship between them. We do this using isogenic lines of the broad-horned flour beetle Gnatocerus cornutus . We observed fighting behavior of paired males of similar body size and age. Using uni- and multivariate mixed models, we show that although there was a significant difference between younger and older males in contest duration, mean aggressiveness was not affected by male age. However, the variation in aggression and fight duration varied with age, being greater in younger and older males respectively. Additionally, although there was a positive correlation between aggressiveness and contest duration in younger males, this relationship was not found in older males. Finally, the only significant genetic effect was for aggression in younger males. Our study shows that age differentially shapes key components of male fighting behavior as well as the relationship among them, highlighting the dynamic nature and context-dependence of fighting.